Finasteride Alleviates High Fat Associated Protein-Overload Nephropathy by Inhibiting Trimethylamine N-Oxide Synthesis and Regulating Gut Microbiota - Wang, Zuoyuan; You, Li; Ren, Yuan; Zhu, Xiaoye; Mao, Xiaoyi; Liang, Xiaowan; Wang, Tingting; Guo, Yumeng; Liu, Te; Xue, Jun (Frontiers in Physiology, 2022)
Unhealthy diet especially high-fat diet (HFD) is the major cause of hyperlipidemia leading to deterioration of chronic kidney diseases (CKD) in patients. Trimethylamine N-oxide (TMAO) is a gut-derived uremic toxin. Our previous clinical study demonstrated that the elevation of TMAO was positively correlated with CKD progression. Finasteride, a competitive and specific inhibitor of type II 5a-reductase, has been reported recently to be able to downregulate plasma TMAO level thus preventing the onset of atherosclerosis by our research group. In this study, we established a protein-overload nephropathy CKD mouse model by bovine serum albumin (BSA) injection to investigate whether hyperlipidemia could accelerate CKD progression and the underlying mechanisms. Finasteride was administrated to explore its potential therapeutic effects. The results of biochemical analyses and pathological examination showed that HFD-induced hyperlipidemia led to aggravated protein-overload nephropathy in mice along with an elevated level of circulating TMAO, which can be alleviated by finasteride treatment possibly through inhibition of Fmo3 in liver. The 16S rRNA sequencing results indicated that HFD feeding altered the composition and distribution of gut microbiota in CKD mice contributing to the enhanced level of TMAO precursor TMA, while finasteride could exert beneficial effects via promoting the abundance of Alistipes_senegalensis and Akkermansia_muciniphila. Immunofluorescence staining (IF) and qRT-PCR results demonstrated the disruption of intestinal barrier by decreased expression of tight junction proteins including Claudin-1 and Zo-1 in HFD-fed CKD mice, which can be rescued by finasteride treatment. Cytokine arrays and redox status analyses revealed an upregulated inflammatory level and oxidative stress after HFD feeding in CKO mice, and finasteride-treatment could alleviate these lesions. To summarize, our study suggested that finasteride could alleviate HFD-associated deterioration of protein-overload nephropathy in mice by inhibition of TMAO synthesis and regulation of gut microbiota.